Ranah Afektif Perspektif Al- Ghazali (Kajian Terhadap Kitab Kimia Saâ€™adah) - Munif, Muhammad Rifqi (CV. Creative Tugu Pena, 2020)
This article was motivated by education in Indonesia which was still focused on cognitive domain. It has the big impact on the round life reality. The aim of this study was to determine the affective domain according to â€œBook of Kimia al-Saâ€Ÿadahâ€ and how the relevance of al-Ghazali's perspective on the affective domain education in Indonesia. The researcher used library research. In collecting the data the researcher used the documentation method which consisted of primary and secondary sources. Primary sources, namely â€œBook of Kimia al-Saâ€Ÿadahâ€ and secondary books, namely